2017
DOI: 10.1002/hep4.1026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel alpha‐fetoprotein‐expressing cell population induced by the Jagged1/Notch2 signal in murine fibrotic liver

Abstract: The liver is well known to possess high regenerative capacity in response to partial resection or tissue injury. However, liver regeneration is often impaired in the case of advanced liver fibrosis/cirrhosis when mature hepatocytes can hardly self‐proliferate. Hepatic progenitor cells have been implicated as a source of hepatocytes in regeneration of the fibrotic liver. Although alpha‐fetoprotein (AFP) is known as a clinical marker of progenitor cell induction in injured/fibrotic adult liver, the origin and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…HSCs were prepared from wild‐type male mice using the Pronase and collagenase perfusion method . In some experiments, HSCs were purified by fluorescence‐activated cell sorting using vitamin A autofluorescence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…HSCs were prepared from wild‐type male mice using the Pronase and collagenase perfusion method . In some experiments, HSCs were purified by fluorescence‐activated cell sorting using vitamin A autofluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) or sirius red‐Fast Green FCF staining was done using standard protocols . For immunofluorescence staining, tissue sections were subjected to optimal antigen retrieval using Target Retrieval Solution (pH 9.0; Dako, Glostrup, Denmark) for 10 minutes at 110°C in an autoclave.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, our data clearly show that the αSMA positive PMFs are located in the PVM adjacent to the BECs at E14.5‐E18.5 and PMFs surrounded the bile duct at P0‐P10, suggesting that PMFs may play an important role in IHBDs development. A recently study reported that αSMA positive myofibroblasts in CCL4‐treated livers expressed Jagged1 (Nakano et al, ). Indeed, the IHC results showed that α‐SMA positive cells expressed Jagged1 in the PVM.…”
Section: Discussionmentioning
confidence: 99%